A clinico-bacteriological study of pyodermas in pediatric population - Awal, Guneet; Kaur, Tanreet (International Journal of Research in Dermatology, 2018)
Background: Pyodermas are frequently confronted skin infections by dermatologists in pediatric population. While treating them recurrence and resistance to commonly used antibiotics are the major concerns. Methods: 456 cases of pyodermas in pediatric population attending dermatology outpatient department of Sri Guru Ram Das Medical College over the period of 8 months from February 2016- October 2016 were evaluated. Samples were collected with sterile swab and sent for gram staining, culture and sensitivity. Results: Majority of cases of pyodermas in pediatric population were due to impetigo and secondarily infected scabies. Most cases were seen in the age group of 4-7 years. Staphylococcus aureus (49.5%) was the most frequently isolated organism from these cases followed by streptococcus (29.8%). Majority of these gram positive organisms were sensitive to antibiotics like amoxiclav, ampicillin and linezolid. E. coli and enterococcus were predominantly encountered gram negative isolates with high susceptibility to aminoglycosides and ceftriaxone. Conclusions: Bacteriological study of pyodermas and knowledge of their susceptibility pattern is imperative for appropriate management. It also helps in prevention of emergence of resistant strains.